You are on page 1of 27

# EXERCISE 1(A)

1.

y 2x 3 13x 2 5x 9

dy
6x 2 26x 5
dx
Let point be (h,k)

k 2h 3 13h 2 5h 9

y 2h3 13h2 5h 9

xh

6h 2 26h 5

substituting 0,0

2.

## 2h3 13h 2 5h 9 6h3 26h 2 5h

4h 3 13h 2 9 0
h 1,k 15.

x a t sin t cos t
y a 1 sin t

dx
a 1 cos 2t
dt

dy
2a 1 sin t cos t
dt
dy 2cos t sin 2t

dx
1 cos 2t

t
t

cos sin

2cos t 1 sin t
2
2

2
t
t
2cos t
cos 2 sin2
2
2
t
2

t
1 tan
2
1 tan

3.

x y
2
a b

nx n 1 ny n 1 dy
n
0
an
b
dx

dy
bn x n 1
n n 1
dx
a y

At a, b
dy
b

dx
a

t
tan
4 2

4.

b x a a y b 0

bx ay 2ab

x y
2.
a b

y be x / a
x0 yb

b
y ' ex / a
a

5.

dy
dx

0,b

b
a

a y b bx

bx y ab

x y
1.
a b

y 3x 2 bx 2
x0

y2

dy
6x b
dx

6.

7.

dy
b4
dx x 0

b4

.... Given

8 x2
2

dy
x 2
dx

x2
y2

y 2 2 x 2 0

2x y 6 0.

[Given]

## Points are p,ap 2 bp c & q,aq 2 bq c

y ap 2 bp c
xp
y ap 2 bp c
xp

a q 2 p2 b q p
qp

aq ap b

8.

y aq ap b x apq c

m aq ap b

&

m 2ax b

dy
dx

pq
2

x y a

1
2 x

dy
0
2 y dx

dy
y

dx
x

Yy
y

Xx
x

X0

Y y xy

Y0

X x xy

x y 2 xy OA OB
9.

x x xy

x y

x2/3+y2/3= a2/3

2
2 dy
1/ 3
0
1/ 3
3x
3y dx

dy
y

dx
x

Yy
y

Xx
x

Y y x 2 / 3 y1 / 3

When X 0

X x x 1/ 3 y 2 / 3

When Y 0

1/ 3

1/ 3

Y 2 X 2 y 2 x 4 / 3 y 2 / 3 2x 2 / 3 y 4 / 3 x 2 2x 4 / 3 y 2 / 3 x 2 / 3 y 4 / 3

x 2 y 2 3x 4 / 3 y 2 / 3 3x 2 / 3 y 4 / 3
x 2 x 4 / 3y2 / 3 y 2 x 2 / 3y4 / 3 2 x 4 / 3y2 / 3 x 2 / 3y4 / 3
x / 3 y 4 / 3 a 2 / 3 2x 2 / 3 y 2 / 3 a 2 / 3
a2 / 3 x 2 / 3 y2 / 3

a2
10.

xy n a n 1

dy
0
dx

y n nxy n 1

dy
y

dx
nx

Yy
y

Xx
nx
y
n

X0

Y y

Y0

X x nx

, n 1

1
1
1

XY xy 1 n 1 , Here n is a constant.
2
2
n

## is constant only when xy is constant but xy n is constant

11.

12.

n 1.

f x 2x 3 9x 2 12x 3

f ' x 6x 2 18x 12 0

x 2 3x 2 0

x ,1 2,

f x x 3 ax 2 48x 19
f ' x 3x 2 2ax 48 0

13.

14.

2a

a 2 144 0

a 12,12

4 3 48 0

f x 2x 3 9x 2 60x 81

f ' x 6x 2 18x 60 0

x 2 3x 10 0

x 2,5

f x

x2
x2

f 'x

2x x 2 x 2
x2

x 2 4x
0
x2

x x 4
0
x 2

x , 4 2,0

15.

16.

17.

f x x2

f ' x x x 1 n x 0

1 n x 0

For x

1
,f 'x 0
e

1
Function decreases in 0, .
e

f x

log x
x

f 'x

log x 1

x e,

1
e

1 log x
0
x2

xe

f x 2 x 2 x 3
For

x2

f x 2 2 x 3 x

7 3x is a decreasing function.
2x 3
f x 2 x 2 3 x

For

x 1 is increasing function.
For
x3

f x 3x 7 is an increasing function.

18.

x 2,

f x cos x sin x

## f ' x sin x cos x 0

x 0,
2

g x cos x sin x
g ' x cos x sin x 0

x 0,
4

x ,
4 2

hx

sin x
x

x cos x sin x
0
x2

h ' x

h '' x

19.

x 0,

## x 2 x sin x 2x x cos x sin x

x

x 0,
2

h' x 0

x
sin x
being reciprocal of
is an increasing function.
sin x
x

f x

a sin x b cos x
c sin x d cos x

f ' x

## a cos x b sin x c sin x d cos x a sin x bcos x c cos x d sin x

2
c sin x d cos x

c sin x d cos x

sin x bx c f x
f ' x cos x b 0 b 1

21.

y 2x 3 3x 2 36x 10 f x
f ' x 6x 2 6x 36 0

x2 x 6 0
x 3 or x 2

f 3 2 27 3 9 36 3 10
71

f 2 2 8 3 4 36 2 10
28 82 54
22.

x 0,
2

20.

at

f x x 2 3x 3

f ' x 2x 3 0

f x has minima at x

3
2

3
3 9 9
f 3
4
2 4 2

f '' x 2 0
3
2

iff

23.

f x 2x 3 3x 2 12x 8
f ' x 6x 2 6x 12 0

24.

x 2 or x 1

f '' x 12x 6

for

x 1

and

for

x2

x 2 is minima

a 2 sec 2 x b2 cos ec 2 x f x
f ' x 2a 2 sec 2 x tan x 2b2 cos ec 2 x cot x 0
f x can have minima only as maxima is .

## a 2 sec 2 x tan x b 2 cos ec 2 x cot x

a2

tan4 x

b2
a2

tan 2 x

b
a
, cot 2 x
a
b

sin x
cos x
b2
3
cos x
sin 3 x

For a, b 0

sec 2 x

ab
ab
, cos ec 2 x
a
b

a 2 sec 2 x b 2 cos ec 2 x
a 2 ab ab b 2 a b

25.

## f x sin x sin x cos x

f ' x cos x cos 2 x sin 2 x 0

cos x 2cos x 1 0

cos x 1

26.

cos x cos 2x

or

cos x

for

for

f x x sin x
f ' x 1 cos x

f '' x sin x

1
2

or
3
3

27.

## f x has neither minimum nor maximum.

a
0
1
1
a cos b sin 1
2
a cos b sin 1

1
2ab sin 2ab cos sin
2

d
ab cos cos 2 0
d

2 cos 2 cos 1 0

cos 1 or cos

1
2

## Now for a triangle,as it will be a st.line, 0 , cos 1

28.

cos

3
3 3 3ab
ab

4
4
2

sin

f ' x 3x 2 6x 6 0

29.

1
2

3
2

for all x

## Neither minimum nor maximum.

4

f x x 6 8 x

Let x 6 t

8 x 14 t

f t t 4 14 t

f ' t 4t 3 14 t 3t 4 14 t 0

t 3 14 t 4 14 t 3t 0

t 3 4 t 56 7t 0

## & f ' x f ' t

3

t 0 or t 14 or t 8
Now t 0 & t 14 as product will become zero
4
3

t 8 & f t 8 .6

30.

x 2 a 2 x a 1 0
a 2, a 1

2 2 a 2 4a 4 2a 2

f a a 2 2a 6

f ' a 2a 2 0

a 1

f a 5 min 2 2

f '' a 0

31.

32.

## Function must be continuous and differentiable to apply Rolles theorem.

33.

f x log sin x

in ,
6 6

5
f f

6
6

f ' x cot x 0 at x

34.

x 2 ab
f x log
in a,b
x a b

f ' x

35.

2x
a b 0

x ab x a b
2

2x 2 x 2 ab
x = GM of a & b.

c 2

1
3

f 1 f 3
2

1 a b 27 9b 3a

and

36.

37.

f x log x in 1,e
f ' x

1
x

1 log e log1
1

c
e 1
e 1

c e 1.

Here,

f 0 f 2 0

f ' c 0

f ' c

1
c

in 0, 2

1
1

3 1
2b 2
a 0
3
3

38.

39.

40.

c 2

2c c 2 0

c 2 3c 2 0

2
as c 0, 2
3

f x x 2 mx n

in

b2 a 2 m b a

f ' c 2x m

2x m b a m

ba

ab
2

## Function should be diffrentiable in domain.

x 1 x

1
x x 1

Now , x N ,
2

x 1 N2

x N, x 1 N

x x 1 2N

1
x x 1

1
2N

EXERCISE 1(B)
1.

y = x1/3(x 1)
dy
4
1 1
1
= x1 3 2 3 2 3 [4x 1]
dx
3
3 x
3x
1
4

## hence f is for x >

2/3
x is always positive and at x 1 / 4
the curves has a local minima

and

1
f for x <
4

now

f ' (x) =

4 1 3 1 2 3
x x
3
3

f '' (x) =

4 1
1 2 1
23 53
9 x
3 3 x

1
2 2 x 1
=
x 9 x 2 3 x

f '' (x) = 0 at x =

1
(inflection point)
2

## (non existent at x = 0, vertical tangent)

2
9x

23

graph of f (x) is as
1

A = x

43

2.

3 3
47
9

=3
=
(D) ]
7 4
28
28

dy
slope fo tangent
dx

3.

3
3

x1 3 dx = x 3 7 x 4 3
7
4
0

1
b

2
t
a

a
t2 0
b

## f (x) = 1 x 4 > 0 in (1, 1) f is

Now f (x) + f ( x) =

x
4

1 t dt

1 t dt

1 t dt

1 y 4 dy ( t = y)

= 0 f (x) is odd
4 x 3

again f (x) =

which vanished at x = 0
2 1 x4
well defined in [1, 1] A, B, C, D ]
4.

## Since intercepts are equal in magnitude but opposite in sign

now

dy
= x2 5x + 7 = 1
dx

x2 5x + 6 = 0

dy
=1
dx P

x = 2 or 3

5.

h (x) =

n f (x ) . g (x)

|x |

sgn x

ax
= 0
a x

6.

n a

|x |

n a a

|x|

.sgn x a |x|.sgn x

n a
sgn x

for x 0
for x 0

= ax sgn x

( {y} + [y] = y)

for x 0

## f (x) = 100 x99 + cosx

for

x (0,1) and 0 , , cosx and x are both +ve
2

x , , x > 1 hence 100 x99 obviously > cosx ]
2
Note that f (x) is continuous at x= 2 and f is decreasing for (2, 3) and increasing for [1, 2] .
At x = 2 f has a maxima hence (A) is not correct. ]

for
7.

8.

9.

## If f and g are inverse then (fog)(x) = x

f ' [g(x)] g ' (x) = 1
if f is increasing

f'>0
sign of g ' is also + ve
If f is decreasing

f'<0
sign of g ' is ve

## since f has an inverse

f is bijective
f is injective
inverse of a bijective mapping is bijective

g is also bijective

g is onto

(D) is correct

10.

(A) is correct
(B) is false

(C) is correct
]

f (x) = ln (1 ln x)
domain (0, e)
f ' (x) =

1
1
< 0 decreasing x in its domain (A) & (B) are incorrect
(1 ln x ) x

f ' (1) = 1
also

## (C) is also incorrect

Lim f ( x ) ; Lim f ( x )

f (1) = 0;

x e 1

x 0

ln x
f '' (x) =

x (1 ln x ) 2

## f '' (1) = 0 which is a point of inflection

graph is as shown
y axis and x = e are two asynmptotes

11.

## f is obvious continuous x R and not derivable at 1 and 1

f ' (x) changes sign 4 times at 1, 0, 1, 2
local maxima at 1 and 1
local minima at x = 0 and 2 ]

12.

Domain is x R

## f (x) = cos tan 1 sin

Also

where cot = x

1
1
= cos tan
2

1 x
1 x2

=
2
2x
g (x) =

1 x2
2 x

= (cos )2 where tan =

1
1 x2

=1

1
2 x2

2x
1
range is , 1 ; f ' (x) =
(2 x 2 ) 2
2
hence f ' (0) = 0

f (x) 1
also Lim
x
hence (B), (C), (D) ]
13.

## Let the tangent line be y = ax + b

The equation for its intersection with the upper parabola is
x2 + 1 = ax + b
x2 ax + (1 b) = 0
This has a double root when a2 4(1 b) = 0
or
a2 + 4b = 4
For the lower parabola
ax + b = x2
x2 + ax + b = 0
This has a double root when a2 4b = 0
subtract these two equations to get 8b = 4 or
b = 1/4
2a2 = 4

2x

1
2

or

a=

and

y=

2x

14.

....(1)

0

....(2)

## 2 f (x) = cos t ( 2 cos x cos t )dt

0

1
2

2
f (x) = cos x cos t dt = 2 cos x
0

f (x) =
15.

(A)

cos

t dt

cos x
Now verify..
2

## Only (A) & (B) are correct.

f (x) = x tan1x

x2

>0

1 x2 1 x2
f (x) > f (0) but f (0) = 0
f (x) > 0

## x > tan1x in (0, 1)

f ' (x) = 1

(B)

(C)

f is increasing in (0, 1)

x2
2
f ' (x) = sin x + x = x sin x > 0 in (0, 1)

f (x) = cos x 1 +

## (B) is not correct

f (x) = 1 + x ln x 1 x 1 x 2

2x
1
1
2 1 x2

f ' (x) = x
2
x 1 x

x
ln x 1 x 2

1 x2

x
ln x 1 x 2
> 0 x R

1 x2
1 x2
(C) is true
=

(D)

f (x) = x

x2
ln (1 x )
2

1
(1 x 2 ) 1
x2
=
=
<0
1 x
1 x
1 x
hence f (x) is decreasing in (0, 1)

## f (x) < f (0)

f ' (x) = (1 x)

f (x) < 0

16.

f ' (x) =

x2
< ln(1 + x) ]
2

2x
x 3
and f '' (x) = 4 . Now interpret
3
x
x

17.

(A)
(B)
(C)

## f (x) has no relative minimum on (3, 4)

f (x) is continuous function on [3, 4]

f '' (x) > 0

## f (x) is concave upwards on [3, 4]

(D) is correct

(D)

18.

f (3) = f (4)
By Rolle's theorem
c (3, 4), where f ' (c) = 0

critical point on [ 3, 4]

## (A) False, e.g. f (x) = sin x

(B) True, from IVT
1
sin 1 1 = sin1(a quantity greater than one) not defined
(C) True as Lim
x
x
(D) True, as the line passes through the centre of the circle.

19.
x

t2

x e dt

0
= Lim
(A) Let = Lim
x 0
x 0 (e x 1) 0
0
x

(B)

x e t dt
0

e
2

x 1

x2

e
= 2 Lim

t2

dt

x 0

x2

e
0
= 2
= 2 Lim
x0 1
0

14x2 7xy + y2 = 2

dy 28x 7 y

....(1)
dx 7 x 2 y
if x = 1 then 14 7y + y2 = 2
hence L (1, 3) and M (1, 4)

y2 7y + 12 = 0

y = 3 or 4

28 21
28 28
= 7 ; slope of tangent at M =
=0
76
7 8
equation of tangent at L and M are
y 3 = 7(x 1)

y = 7x 4
and
y 4 = 0(x 1)

y=4

slope of tangent at L =

(C)

8
hence N = , 4
(C)
7
If n is odd then graph of f (x) is

## a3 is the only point where

f (x) has its minimum value

a1

a2

a3

a4

a1

a2

a3

a4

a5

## If n is even then graph of f (x) is

From a2 to a3 at all values of x, f (x) is minimum.
2

(D)
20.

ab
(la my)
= l(b2 a2) + m(b a) = l(b + a) + m; c =
2
ba
4
4
We have f ' (x) = 5 sin x cos x 5 cos x sin x = 5 sin x cos x(sin x cos x)(1 + sin x cos x)

## 2lc + m = (lb2 + mb)

f ' (x) = 0 at x =

## . Also f ' (0) = f ' = 0

4
2

Hence some c 0, for which f ' (c) = 0 (By Rolle's Theorem)
2

(C) is correct.

Also in 0, f is decreasing and in , f is increasing
4 2
4

As

f (0) = f = 0
2

2 roots

minimum at x =

(D) is correct.]

21.

f (x) = tan1(x) is defined on R and is strictly increasing but do not have its range R]

22.

f (0) = 1; f (2) = 2
f (1) =f (1+) = f (1) = 2 ]

23.

f (x) = ln(2 + x)

2x 2
is continuous in (2, )
x3

1
4
( x 3) 2 4( x 2)
f ' (x) = x 2
2 =
( x 3)
( x 2)( x 3) 2
x 2 2x 1
( x 1) 2
=
>0
( x 2)(x 3) 2
( x 2)(x 3) 2
f is increasing in ( 2, )

(f ' (x) = 0 at x = 1)

f ( x ) and Lim f ( x )
also xLim
x
2

unique root]

24.

Let f (x) = 0 has two roots say x = r1 and x = r2 where r1, r2 [a, b]

f (r1) = f (r2)
hence there must exist some c (r1, r2) where f ' (c) = 0
but f ' (x) = x6 x5 + x4 x3 + x2 x + 1
for |x| 1,
f ' (x) = (x6 x5) + (x4 x3) + (x2 x) + 1 > 0
for |x| 1,
f ' (x) = (1 x) + (x2 x3) +(x4 x5) + x6 > 0
hence f ' (x) > 0 for all x

## Rolles theorem fails

f (x) = 0 can not have two or more roots.]

25.

## Consider the example of f (x) = ex and f ' (x) = ex both increasing]

Paragraph for question nos. 26 to 27

(i)

2x

We have f(x) = x
So,
f '(x) = 2x (1 x ln2)
and
f "(x) = 2x ln2 (x ln 2 2)
1

, .
Clearly, f(x) is increasing in ,
and decreasing in
ln 2
ln 2

y
1
e ln2

1
ln2

Graph of f(x) = x 2

(ii)
(iii)

1
.
Clearly, f(x) = k has two distinct roots for k 0,
e ln 2
Given f(x) = x 2x and g(x) = max. {f(t) : x t x + 1}
1

As f(x) is increasing in ,
, hence maximum value of g(x) occurs at t = x + 1
ln 2

g(x) = f (x + 1) = (x + 1) 2 (x + 1)
1
1
ln 2

( x 1)

## g(x) dx = (x1) 2II dx

Let I =

I
( I.B.P.)

1
( x 1) ln 2 1

( x 1) 2
ln 2

0
1

( x 1) (x1) ln 2
2
=

ln 2
0
=

1
ln 2

1
1
ln 2
(x 1)

dx

0
1

ln 2
2 2( x 1)
ln 2
0

1 1 1 1
1 1 1
1
1
1
1
2 =
+

2
2
ln 2 ln 2 e 2
ln 2 e 2
e ln 2 2 ln 2 e ln 2 2 ln 2 2

1
2 ln 2 2

1
2

Ans.]
2 ln 2 e ln 2 2

(1)

1
Lim x ln 1 = Lim
x 0
x x 0

x 1
ln

x
1
x

## Using L'Hospital's Rule

(2)

1
x
1 2
1
1
1
x 2 = Lim
x = Lim
x 2 = Lim
l = Lim
= 0 Ans.
x 0 x ( x 1)
x 0 ( x 1)
x 0 x
x 1
x 0
x 1 x
Lim f ( x ) 1 (can be verified)
x 0

Lim f ( x ) e
x

## f is increasing for all x > 0 (D) (can be verified)

Also
(3)

n n k
l = 1
k 1 k
taking log,

n 1 n

1 n
n
ln l = Lim ln 1
n n
k
k 1
1

{given f (x) = (1 +

kn

1/x)x

n
and f (k/n) = 1
k

1 n k
1
dx
= Lim ln 1
n n
k n
k 1 n
1

1
2
1
1 x2
1 x
1
= x
ln1 dx = ln 1
dx
x

x 2 0 0 x x 1 2
0 II

k n

1
1
1
1 x 11
dx = ln 2 x ln (x 1)10
= ln 2 0
2
2
2
2 0 x 1

1
1
1
ln 2 (1 ln 2) 0 =
2
2
2

l=

e
Paragraph for question nos. 32 to 34

y=

x 2 1

=1+

; not defined at x = 1

1
;
x 1

y'=

2x
( x 1) 2
2

dy
=0

x = 0 (point of maxima)
dx
as
x 1+, y
;
x 1 , y
|||ly
x 1+, y ;
x 1 , y

The graph of y =

x2

is as shown
x 2 1
verify all alternativels from the graph.

## Paragraph for question nos. 35 to 37

(i)

a=1
f(x)=8x3 + 4x2 + 2bx + 1
f ' (x) = 24x2 + 8x + 2b = 2(12x2 + 4x + b)
for increasing function,
f ' (x) 0 x R

D0
16 48b 0

(ii)

(C)

if b = 1
f (x) = 8x3 + 4ax2 + 2x + a
f ' (x) = 24x2 + 8ax + 2
or
2(12x2 + 4ax + 1)
for non monotonic f ' (x) = 0 must have distinct roots
hence D > 0 i.e.
16a2 48 > 0
a2 > 3;

(iii)

a > 3 or a < 3
a 2, 3, 4, .......
sum = 5050 1 = 5049 Ans.
If x1 , x2 and x3 are the roots then log2x1 + log2x2 + log2x3 = 5
log2(x1x2x3) = 5
x1x2x3 = 32
a
= 32
8
a = 256 Ans. ]

38.

## (A) R; (B) R, S, T ; (C) Q; (D) Q

2 1

(A)

I=

( x 2 1) 2 (x 2 1)
( x 2 1) 2

2 1

2 1

( x 2 1)

( x 2 1) 2 dx = 2

2 1

dx =

2 1

( x 2 1)

dx
( x 2 1) 2

2 1

I1

I1 =

(x 2 1)2 dx

where (a =

1a

1a

( x 2 1)

1
1
1
t2
2 dt =
2
1
t
2 1
t

2 1) ;

1a

put x =

(1 t 2 ) t 4
dt =
t 4 (1 t 2 ) 2

1
1
dx = 2 dt
t
t
1a

(1 t 2 )
dt =
(1 t 2 ) 2

1a

t 2 1
dt
( t 2 1) 2

t 2 1
= ( t 2 1) 2 dt = I1
1a

(B)

(C)

2I1 = 0
I1 = 0
Domain of f (x) is (0, 1) (1, )
ln f (x) = 1

f (x) = e = constant
f ' (x) = 0, for all in (0, ) {1}
Clearly (1, 0) is the point of intersection of given curves.
2x
+ 2x (ln2) (lnx)
x
Slope of tangent to the curve f (x) at (1, 0) = m1 = 2

Now, f '(x) =

d 2x lnx
(e
1) = x2x 2 x 2 lnx
x

dx

## Slope of tangent to the curve g (x) at (1, 0) = m2 = 2

since m1 = m2 = 2

## Two curves touch each other, so angle between them is 0.

Hence cos = cos 0 = 1
y
3y2y' 3y 3xy' = 0
y' = 2
y x
y' = 0
y = 0, no real x.
y' =
y2 = x
y3 = 1, y = 1
The point is (1, 1)

Similarly,

(D)

g'(x) =

39.

## (A) R,(B) Q,(C) P,(D) S

(A)

dy 4t
,
dx 3

x-intercept

4
Tangent is y at

4t
x at 3
3

at 3
4
4

y-intercept at
3

at 3
at 4
, 0 and 0,
the point of intersection of tangent with the axes are
3
4

at 4
A 0,

at 3
B
,0
4

at 2 ,at 4

P divids AB externaly in 4 : 3
m 4

m4 & n3
n 3
as m & n are coprime to each other

mn 7

(B)

dx
esin y cos y : slope of normal 1
dy
equation of normal is x y 1
Area

(C)

1
2

1 dy
1
:
3 : slope of tangent 2
2
x dx
x

y e2 2 x :

dy
e 2 2 x . 2 : slope of tangent 2
dx

tan 0

y
be x / 3

3
y ' b 1 ex/3
2

(D)

Length of subtangent

40

## (A) (q),(B) (r),(C) (q),(D) (q)

y f x

1
so y 0
x

1
Now f y f f y 1 also f x f y 1
y

1
f x f f y
y

1
f

f x f x 1/ x

## also f(x) is increasing

1
1

f x f x 1/ x

f x

1 5
2x

now f x

1 5
1 5
is decreasing so discarding it f x
.
2x
2x

Exercise 1(C)
1

## Given S = x2 + 4xh = 1200

and
V = x 2h
1
x 2 (1200 x 2 )
;
V(x) = (1200x x3)
4
4x
Put V ' (x) = 0 gives x = 20
If
x = 20, h = 10
Hence Vmax. = x2h = (400) (10) = 4000 cubic cm.

V(x) =

## Note that C1 is a semicircle and C2 is a rectangular hyperbola.

PQ will be minimum if the normal at P on the semicircle is also a
normal at Q on xy = 9
Let the normal at P be y = mx
....(1) (m > 0)
solving it with xy = 9
3
9 m
mx2 = 9

x=
; y=
m
3
3

,3 m

Q
3

differentiating xy = 9
dy
dy
y
x
+y=0
=
dx
dx
x
dy
3 m m

=m
dx Q =
3

## tangent at P and Q must be parallel

1

m=

m2 = 1
m

normal at P and Q is y = x
solvingP(1, 1) and Q(3, 3)

(PQ)2 = d2 = 4 + 4 = 8 Ans. ]
3

m=1

The given expression resembles with (x1 x2)2 + (y1 y2)2, where y1 =

x12
and
20

y2 =

(17 x 2 )( x 2 13)
Thus, we can thing about two points P 1(x 1, y1) and P2(x 2, y2) lying on the curves x 2 = 20y and
(x 15)2 + y2 = 4 respectively.
Let D be the distance between P1 and P2 then the given expression simply represents D2.
Now, as per the requirements, we have to locate the point on these curves (in the first quadrant) such
that the distance between them is minimum.
Since the shortest distance between two curves always occurs along the common normal, it implies that
we have to locate a point P(x1, y1) on the parabola x2 = 20y such that normal drawn to parabola at this
point passes through (15, 0).

x12
10

## (x x1) . It should pass

Now, equation of the normal to the parabola at (x1, y1) is
=

20
x1

## x13 + 200x1 3000 = 0

D=

(10 15) 2 52 2 = 5 2 2

x1 = 10

y1 = 5

## The minimum value of the given expression is 5 2 2 2 = a 2 b

a5&b2

x = t2 ; y = t3
dx
dy
= 2t ;
= 3t2
dt
dt
dy
3t
=
dx
2
3t
(x t2)
2
2k 2t3 = 3th 3t3

y t3 =

....(1)

t 3 3th 2k 0
(put t1t2 = 1);
hence t3 = 2k
now t3 must satisfy the equation (1) which gives 4y2 = 3x 1.
Comparing with ay2 = bx 1 , we have a = 4 and b = 3.
t1 t 2 t 3 2k

2 x log 1 (k 2 6 k 8), 2 x 1

We have F(x) =
2
x 3 3x 2 4 x 1 ,
1 x 3
Also F(x) is increasing on [1, 3] because F '(x) > 0 x [1, 3].
And F '(x) = 2 x [2, 1), so F(x) is decreasing on [2,1).

Lim F(1 h ) F(1)
h 0

## 2 + log1/2 (k2 6k + 8) 1 log1/2(k2 6k + 8) 3 k2 6k + 8 8

k2 6k 0 k [0, 6]
....(1)
2
But in order to define log1/2(k 6k + 8),
We must have k2 6k + 8 > 0

(k 2) (k 4) > 0

k < 2 or k > 4
......(2)

## Possible integer(s) in the range of k are 0, 1, 5, 6

Hence the sum of all possible positive integer(s) in the range of k = 1 + 5 + 6 = 12 Ans. ]

x3
+ (a 3) x2 + x 13
3
For F(x) to have negative point of local minimum, the equation F '(x) = 0 must have two distinct
negative roots.
Now, F '(x) = x2 + 2(a 3) x + 1

## Following condition(s) must be satisfied simultaneously.

(i)
Discriminant > 0;
(ii)
Sum of roots < 0 ;
(iii)
Product of roots > 0
Now, D > 0

## 4(a 3)2 > 4

(a 3)2 1 > 0 (a 2) (a 4) > 0

a ( , 2) (4, )
........... (i)
Also 2(a 3) < 0
a3>0

## a > 3 .......... (ii)

And product of root(s) = 1 > 0 a R

## (i) (ii) (iii)

a (4, )
....(iii)
Hence sum of value(s) of a = 5 + 6 + 7 + ......... + 100 = 5040
Ans. ]

We have F(x) =

7.

Consider y = x +

1
3
x

dy
1
1 2 = 0
dx
x

5
y=p3

As

dy
0

x = 1 or 1
dx
x 0+, y and x 0, y

1
Also roots of x 3 = 0 x2 3x + 1 = 0
x
3 94
3 5
=
2
2
For two distinct solutions either p 3 = 0 p = 3
or
1<p3<5
4<p<8
Hence p {3} (4, 8)
p = {3, 5, 6, 7}

Sum = 21 Ans. ]

x=

O
(0, 0)

3 5
Where A

3 5

and B

x2

## Let f ''(x) = 6a (x 1) (a > 0) then f '(x) = 6a

x + b = 3a(x2 2x) + b.
2

## f '(x) = 3a (x2 2x 3) = 0 x = 1 and 3.

So
y = f(1) and y = f(3) are two horizontal tangents.
Hence distance between its two horizontal tangents = |f(3) f(1)| = |22 10| = 0032. Ans. ]

Volume (V) =
|||ly

1
A1 h1
3

3V
h1 = A
1

3V
3V
3V
h2 = A , h3 = A and h4 = A
2
3
4

3V 3V 3V 3V

## So (A1+A2+A3+A4)(h1 + h2 + h3 + h4) = (A1+A2+A3+A4)

A1 A 2 A 3 A 4

1
1
1
1

= 3V(A1+A2+A3+A4)
A1 A 2 A3 A 4
Now using A.M.-H.M inequality in A1, A2, A3, A4, we get
A1 A 2 A 3 A 4
4

4
1
1
1
1

A1 A 2 A 3 A 4

1
1
1
1
16

(A1+A2+A3+A4)
A1 A 2 A3 A 4
Hence the minimum value of (A1+A2+A3+A4)(h1+h2+h3+h4) = 3V (16) = 48V = 48 5 = 240 Ans. ]
10

y = x2 and y =

8
;
x

q = p2 and s =

8
r

....(1)

dy
at A and B, we get
dx

Equating

y
f(x)=x2
A(p,q)

8
2p = 2
r

pr2 = 4

....(1)

O
B(r, s)

8
p
q s
r
mAB =
2p =
pr
pr
2

Now

16

p2 = 2pr +

16
8
p2 =
r
r

16
r = 1 (r 0) p = 4
r
r

r = 1, p = 1
Hence p + r = 5

11

x = 0 and x = 1 ]

12

y = x2
dx
dy
= 2x .
dt
dt
dx
dt

= 10m/sec.

tan =

x2
=x
x

sec2 .

d dx
=
dt
dt

d
1
= 10 cos2 = 10
=1
10
dt
13

3x2 2y

dy
=0
dx

{ at x = 3m }

3x2
dy
=
2y
dx

## slope of tangent at (4a2 , 8a3) =

3(16 a 4 )
2( 8a 3 )

= 3a

let this tangent at this point also cuts the curve at (4b2, 8b3) and normal at this point slope of
1
.
3b

3a =

1
ab = 1 ......(i)
9
3b

slope of line =

8a 3 8b 3
2

4a 4b

2(a3 b 3 )
2

(a b )

## = 3a [it is equal to slope of target]

2a2 + 2b2 + 2ab = 3a2 + 3ab
2b2 = a2 + ab

2
81a

a2 1
9

2(a2 b2 ab)
ab

2 = 81a4 9a2
81a4 9a2 2 =0
81a4 18a2 + 9a2 2 = 0
9a2 (9a2 2) + (9a2 2) = 0
(9a2 2) (9a2 + 1) = 0
9a2 = 2
14.

## Let x = r cos and y = r sin

y

r2 = x2 + y2; tan =
(0, /2)
x
r2
r2
2
N= 2
=
=
5 sin 2 3 cos 2
r [cos 2 sin cos 4 sin 2 ]
(1 cos 2) sin 2 4(1 cos 2)
Nmax =
Nmax =
A=

15.

16.

2
5 10
2
5 10

2
5 10 = M
15

2
5 10 = m
15

2 10
Mm
2
= 15 2 =
2
3

2007

2
= 1338 Ans. ]
3

f (3)
23 k 9
1
= 6k
= ;
f (9) f (3) = (29k + 9) (23k + 9) = 29k 23k
f ( 6)
3
2 9
3(23k + 9) = 26k + 9

26k 3(23k) 18 = 0
23k = y
y2 3y 18 = 0
(y 6)(y + 3) = 0
y = 6; y = 3 (rejected)
23k = 6
now f (9) f (3) = 29k 23k { from (1) }
= (23k)3 23k
= 63 6 = 210
hence N = 210 = 2 3 5 7
Total number of divisor = 2 2 2 2 = 16
number of divisors which are composite = 16 (1, 2, 3, 5, 7) = 11 Ans. ]
f (3) = f (3) = 2
[ f (x) is an even function,
again f (1) = f (1) = 3

2 | f (1) | = 2 | f (1) | = 2 | 3 | = 6
from the graph,

f ( x) = f (x) ]

7
3< f <2
8

7
f 8 = 3

f (0) = 0
(obviously from the graph)
cos1 f (2) = cos1 f (2) = cos1(1) = 0
f (7) = f ( 7 + 8) = f (1) = 3
[f (x) has period 8]
f (20) = f (4 + 16) = f (4) = 3 [ f (nT + x) = f (x) ]

....(1)

sum = 2 + 6 3 + 0 + 0 3 + 3

sum = 5
17

## f '(x) = (b 1) (b 2) ( 2 sin 2x) + (b 1)

Now, f '(x) 0 for every x R,
so

(b 1) 1 2( b 2) sin 2x 0 x R
b1

5
1
3
> 1 b , 2 2,
2( b 2)
2
2
Now, when b = 2, f(x) = x + sin 2 f '(x) = 1 ( 0).

Also,

3
Hence, b ,
2

18.

(b1 + b2) =

b1 =

3
5
and b2 =
2
2

3 5 8
= =4
2 2
2

## Let x = r cos and y = r sin

E = (x + 5)(y + 5) = (r cos + 5)(r sin + 5) = r2 sin cos + 5r(cos + sin ) + 25
Now put x = r cos and y = r sin in x2 + xy + y2 = 3

6
3
=
2 sin 2
1 sin cos

## hence r2]min. = 2 + sin 2]max. = 3 occurs at sin 2 = 1 2 =

Hence E =

put

5
or
i.e.
or
2
2
4
4

r2
(sin 2) + 5r(cos + sin ) + 25
2

r2 = 2 and =

1
1

+ 25 = 36
E=1+ 5 2
2
4
2

1
1

+ 25 = 16
E = 1 + 5 2
2
2
4

put

19.

r2 = 2 and =

f (2) f (1)
= f ' (c) 2
2 1
f (2) f (1) 2

c (1, 2)

f (2) 4

f ( 4) f ( 2)
= f ' (d) 2
42

f (4) f (2) 4
8 f (2) 4
4 f (2)

f (2) 4
from (1) and (2)
f (2) = 4

d (2, 4)

....(2)

....(1)

20.

## Let x tree be added then

P(x) = (x + 50) (800 10x)
now P'(x) = 0

x = 15